1995
DOI: 10.1007/bf00203637
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid enhances the activity of the alternative pathway of respiration in tobacco leaves and induces thermogenicity

Abstract: A rise in the level of endogenous salicylic acid (SA) during flowering of the thermogenic voodoo lily, Sauromatum guttatum, leads to a pronounced temperature elevation by stimulation of the alternative respiratory pathway. We have studied the thermal response of tobacco (Nicotiana tabacum L.) leaves, a non-thermogenic tissue, to exogenous SA, and its relation to alternative respiration. A reproducible increase in surface temperature of 0.5-1.0 degrees C was registered with high-resolution infrared cameras. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
2
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 32 publications
(36 reference statements)
2
27
2
1
Order By: Relevance
“…The results of the present study suggst that there is an apparent regulation of the alternative oxidase that compensates for the higher amount of alternative oxidase protein present to keep the partitioning of electrons to the oxidase constant at a given total respiration rate. The respiratory data from this study differ from the results obtained by Van Der Straeten et al (1995). Eight hours after SA treatment of tobacco plants, these authors observed an increase in the total respiration rate, as well as an increase in the activity of the alternative pathway measured as the difference between total respiration and the respiration after the addition of 25 mM SHAM.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The results of the present study suggst that there is an apparent regulation of the alternative oxidase that compensates for the higher amount of alternative oxidase protein present to keep the partitioning of electrons to the oxidase constant at a given total respiration rate. The respiratory data from this study differ from the results obtained by Van Der Straeten et al (1995). Eight hours after SA treatment of tobacco plants, these authors observed an increase in the total respiration rate, as well as an increase in the activity of the alternative pathway measured as the difference between total respiration and the respiration after the addition of 25 mM SHAM.…”
Section: Discussioncontrasting
confidence: 99%
“…The rate of O, consumption for untreated plants obtained in this study is higher than that reported by Van Der Straeten et al (1995), the difference being approximately 35 nmol O, min-' g-' fresh weight, perhaps due to varietal differences. The respiration rates reported by Van Der Straeten et al (1995) following treatment with SA (approximately 90 m o 1 O, min-' g-' fresh weight) are closer to the rates obtained in our experiments for both treated and untreated plants. It is possible that the increase in respiration rate observed by Van Der Straeten et al (1995) was due to the different method of application of SA to their plants.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations